Climate policy integration in the land use sector: Mitigation, adaptation and sustainable development linkages. Issue 67 (January 2017) - Di Gregorio, Monica; Nurrochmat, Dodik Ridho; Paavola, Jouni; Sari, Intan Maya; Fatorelli, Leandra; Pramova, Emilia; Locatelli, Bruno; Brockhaus, Maria; Kusumadewi, Sonya Dyah
Highlights: CPI in the land use sector requires reconciling mitigation and adaptation goals. A lack of governmental supervision hampers CPI progress. Addressing mitigation and development trade-offs is necessary for CPI in Indonesia. More knowledge and capacity on adaptation is needed for effective CPI in land use. Abstract: This article re-conceptualizes Climate Policy Integration (CPI) in the land use sector to highlight the need to assess the level of integration of mitigation and adaptation objectives and policies to minimize trade-offs and to exploit synergies. It suggests that effective CPI in the land use sector requires i) internal climate policy coherence between mitigation and adaptation objectives and policies; ii) external climate policy coherence between climate change and development objectives; iii) vertical policy integration to mainstream climate change into sectoral policies and; iv) horizontal policy integration by overarching governance structures for cross-sectoral coordination. This framework is used to examine CPI in the land use sector of Indonesia. The findings indicate that adaptation actors and policies are the main advocates of internal policy coherence. External policy coherence between mitigation and development planning is called for, but remains to be operationalized. Bureaucratic politics has in turn undermined vertical and horizontal policy integration. Under these circumstances it is unlikely that the Indonesian bureaucracy can deliver strong coordinated action addressing climate change in the land use sector, unless sectoral ministries internalize a strong mandate on internal and external climate policy coherence and find ways to coordinate policy action effectively.